2016
DOI: 10.3847/0004-637x/819/2/93
|View full text |Cite
|
Sign up to set email alerts
|

Spitzer Parallax of Ogle-2015-BLG-0966: A Cold Neptune in the Galactic Disk

Abstract: We report the detection of a cold Neptune m planet =21±2 M ⊕ orbiting a 0.38 M e M dwarf lying 2.5-3.3 kpc toward the Galactic center as part of a campaign combining ground-based and Spitzer observations to measure the Galactic distribution of planets. This is the first time that the complex real-time protocols described by Yee et al., which aim to maximize planet sensitivity while maintaining sample integrity, have been carried out in practice. Multiple survey and followup teams successfully combined the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(56 citation statements)
references
References 48 publications
0
56
0
Order By: Relevance
“…Finally, we note that Swift might be able to detect the parallax signal during caustic crossings (in particular the caustic exits) of bright binary events (analogous to the original idea presented by Honma 1999), which are much more common, and with real-time light curve modeling it can be predicted in advance to trigger Swift. A thorough study of Swift microlens parallax sensitivity will be conducted in R.A. Street et al 2016, (in preparation).…”
Section: Swift Feasibility Of Microlens Parallax Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we note that Swift might be able to detect the parallax signal during caustic crossings (in particular the caustic exits) of bright binary events (analogous to the original idea presented by Honma 1999), which are much more common, and with real-time light curve modeling it can be predicted in advance to trigger Swift. A thorough study of Swift microlens parallax sensitivity will be conducted in R.A. Street et al 2016, (in preparation).…”
Section: Swift Feasibility Of Microlens Parallax Measurementsmentioning
confidence: 99%
“…Simultaneous ground and space observations of microlensing events were conducted only twice prior to these campaigns, once with Spitzer (Dong et al 2007), and once with the Deep Impact (or EPOXI) spacecraft (Muraki et al 2011). The 2014-2015 Spitzer campaigns have already led to the detection of two planets Street et al 2016), the first causticcrossing binary-lens event with a satellite parallax measurement (Zhu et al 2015b), a massive remnant in a wide binary (Shvartzvald et al 2015), and mass measurements of isolated objects (Zhu et al 2016)-one of which is a brown dwarf (BD). In addition, Spitzer observations allowed Bozza et al (2016) to break a strong planet/binary degeneracy in the event OGLE-2015-BLG-1212, finding that the companion is a low-mass star and not a planet.…”
Section: Introductionmentioning
confidence: 99%
“…One event, MOA-2011-BLG-293Lb, was determined to be located in the Galactic bulge by measuring the lens flux (Yee et al 2012;Batista et al 2014), but Bhattacharya et al (2017) and Koshimoto et al (2017) have shown that there can be ambiguity in the interpretation of these apparent lens detections. The recent simultaneous observations from the Spitzer space telescope helped to measure the space-based parallax and contribute to the determination of the distance to the lens system (Street et al 2016). However, the statistical sample of microlensing planets is not yet large enough to draw a clear picture.…”
Section: Introductionmentioning
confidence: 99%
“…Although the Spitzer microlensing program has been successful in terms of measuring masses of individual planetary systems Street et al 2016; Ryu et al 2017;Shvartzvald et al 2017) and constraining the Galactic distribution of planets (Calchi Novati et al 2015a;Yee et al 2015a;Zhu et al 2017b), there is a generic uncertainty in measuring p E with a single satellite, especially in cases of single-lens events. The microlensing parallax vector p E is directly related to the displacement between the two lenssource relative trajectories…”
Section: Introductionmentioning
confidence: 99%